2020
DOI: 10.1186/s41687-020-0186-2
|View full text |Cite
|
Sign up to set email alerts
|

Childhood vitiligo impacts emotional health of parents: a prospective, cross-sectional study of quality of life for primary caregivers

Abstract: Background/objectives: Individuals with vitiligo have an increased risk of depression, anxiety, social isolation and detrimental effects on body image/self-esteem. However, assessments of quality of life (QoL) impact have not focused on caregivers of children with vitiligo. To address this, we determined the QoL impact in parents of children with vitiligo to assess the relationship between QoL parameters and disease duration, location, and severity. Methods: We performed a cross-sectional study involving 123 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
1
20
1
1
Order By: Relevance
“…Caregiver (e.g., parents, sibling, spouse) burden and associated factors were discussed in ten articles [ 20 , 24 , 53 , 64 , 86 , 103 , 111 , 121 , 139 , 172 ], although only four provided prevalence rates [ 64 , 86 , 103 , 111 ] for aspects of psychosocial burden. Overall QoL among caregivers was impaired, with depression, anxiety, emotional distress, and impaired social life commonly mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…Caregiver (e.g., parents, sibling, spouse) burden and associated factors were discussed in ten articles [ 20 , 24 , 53 , 64 , 86 , 103 , 111 , 121 , 139 , 172 ], although only four provided prevalence rates [ 64 , 86 , 103 , 111 ] for aspects of psychosocial burden. Overall QoL among caregivers was impaired, with depression, anxiety, emotional distress, and impaired social life commonly mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in one study, the severity of vitiligo in adolescents was observed to affect QoL negatively 16 while two other studies including children and adolescents reported no relationship between QoL and the body surface area 36 and vitiligo severity 15 . According to another study in which the effect of childhood vitiligo on parents' QoL was examined, as the area of involvement of vitiligo increased, the parental QoL decreased 37 . In the current study, we found no correlation between disease severity and the QoL of patients or parents.…”
Section: Discussionmentioning
confidence: 99%
“…The Northern Hospital, Melbourne, Vic., Australia, 2 Royal Melbourne Hospital, Melbourne, Vic., Australia, 3 Department of Dermatology, AP-HP, Henri Mondor Hospital, UPEC, Cr eteil, France, 4 EpiDermE, Universit e Paris-Est Cr eteil (UPEC), Cr eteil, France, 5 Chroma Dermatology, Pigment and Skin of Colour Centre, Melbourne, Vic., Australia, 6 Department of Dermatology, The Royal Children's Hospital, Parkville, Vic., Australia, 7 Department of Paediatrics, The University of Melbourne, Parkville, Vic., Australia *Correspondence: M. Rodrigues. E-mail: dr.rodrigues@gmail.com…”
Section: Funding Sourcesmentioning
confidence: 99%